Comparative Analysis of FIFO and LRU Memory Management Algorithms Using CPU-OS Simulator v7.5.50: Kajian Komparatif terhadap Algoritma Manajemen Memori FIFO dan LRU Menggunakan CPU-OS Simulator v7.5.50 - Mursid Dwi Hastomo; Setyawan Widyarto (RADIANT: Journal of Applied, Social, and Education Studies, 2026)
Efficient memory management is a critical aspect of operating system performance, as poor management can lead to high page fault rates, increased execution time, and reduced CPU utilization. This study examines the performance comparison of two widely used memory management strategies, First-In-First-Out (FIFO) and Least Recently Used (LRU), using simulations conducted through the CPU-OS Simulator v7.5.50. The objective is to observe differences in page fault rate, execution time, and CPU efficiency across various scenarios. Three experiments were conducted: first, the impact of cache/pipeline configuration; second, the influence of process scheduling on memory management; and third, the effect of memory size and page access patterns. The results show that LRU tends to provide a lower page fault rate under heavy workloads, while FIFO demonstrates advantages when memory is limited and overhead is minimal. This study contributes to understanding how page replacement algorithms affect system performance in an operating system simulation environment.